YOUTH TUBERCULOSIS TROOPS: MOBILIZING CASE FINDING FOR TB ELIMINATION IN INDONESIA (Proceedings of the International Conference on Public Health, 2025)
This research explores the role of adolescents in tuberculosis (TB) prevention through the Laskar TB (Youth Tuberculosis Troops) program in Indonesia. A qualitative research design was employed, with data collected from 52 adolescent volunteers and committee members of the organization through in-depth interviews and focus group discussions. The study highlights the success of the “Goes To School” program, which effectively increased adolescents’ knowledge about TB and empowered them to become health advocates by disseminating information within their communities. The study also examined the recruitment methods used to attract participants, noting that a combination of formal and informal approaches proved to be effective in engaging youth. However, challenges were identified in sustaining member participation, as many adolescents did not consistently engage in the program’s activities. Despite these challenges, the study concludes that engaging adolescents as active participants and change agents in health education can significantly contribute to raising awareness about TB and advancing the goal of TB elimination. The findings suggest that youth-led initiatives, when properly structured and supported, can play a crucial role in community-based health interventions.
Keywords: tuberculosis; adolescents; health education; laskar TB; community participation; peer education; TB elimination strategies